Optimizing Human Capital in Industry 5.0: A Structural Analysis of the Effects of Work Ethics, Motivation, and Job Satisfaction on Employee Performance - Nenah Sunarsih; Irmawaty Irmawaty; Andriyansah Andriyansah (Society, 2025)
The emergence of Industry 5.0, which integrates advanced technology with a human-centered approach, has significantly reshaped organizational dynamics. This transformation underscores the critical role of human resources in sustaining organizational competitiveness. Employee performance is not solely determined by output quantity but also by output quality. Employees must operate effectively and efficiently to optimize organizational performance. This study examines the impact of work ethic, motivation, and job satisfaction on employee performance. The research population comprises all employees at Indonesia Open University (IOU), with the sample drawn from IOU’s central office and the Bandung and Yogyakarta regional offices, yielding 179 valid responses. A quantitative approach utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed for data analysis. The findings indicate that work ethic has a significant positive effect on employee performance—employees with a stronger work ethic exhibit higher performance levels. Conversely, motivation and job satisfaction do not exhibit a statistically significant effect on employee performance. Collectively, work ethic, motivation, and job satisfaction explain 56.4% of employee performance variance, while the remaining 43.6% is influenced by other external factors beyond the study’s scope.